Rheological and Electrical Study of a Composite Material Based on an Epoxy Polymer Containing Cyclotriphosphazene - Dagdag, O.; El Gouri, M.; El Mansouri, A.; Outzourhit, A.; El Harfi, A.; Cherkaoui, O.; El Bachiri, A.; Hamed, O.; Jodeh, S.; Hanbali, G.; Khalaf, B. (Polymers, 2020)
In this work, we have studied, formulated, prepared, and characterized the rheological and electrical behavior of a composite material based on an epoxy resin Diglycidyl Ether of Bisphenol A (DGEBA) reinforced with hexaglycidyl cyclotriphosphazene (HGCP). The epoxy system was cured with 4,4’-methylene dianiline (MDA). DGEBA-HGCP-MDA epoxy composite materials with reinforced HGCP which varied from 5% to 10% by weight were prepared by mixing in the molten state. The morphology was evaluated by SEM. The rheological behavior was studied using small deformation rheology. The electrical characterization was carried out with a frequency variation range from 1 Hz to 100 KHz at room temperature. These measurements revealed that the rheological and electrical behaviors strongly depend on the quantity of HGCP in the DGEBA matrix. The linear viscoelastic properties study reveals that the modulus of elasticity G’ is dependent on the amount of HGCP present in the epoxy resin DGEBA. The capacitance-frequency measurements suggest a distribution of localized states in the band gap of the blends.